Combination of a Gellan Gum-Based Hydrogel With Cell Therapy for the Treatment of Cervical Spinal Cord Injury - Gomes, Eduardo D.; Ghosh, Biswarup; Lima, Rui; Goulão, Miguel; Moreira-Gomes, Tiago; Martins-Macedo, Joana; Urban, Mark W.; Wright, Megan C.; Gimble, Jeffrey M.; Sousa, Nuno; Silva, Nuno A.; Lepore, Angelo C.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Cervical spinal cord trauma represents more than half of the spinal cord injury (SCI) cases worldwide. Respiratory compromise, as well as severe limb motor deficits, are among the main consequences of cervical lesions. In the present work, a Gellan Gum (GG)-based hydrogel modified with GRGDS peptide, together with adipose tissue-derived stem/stromal cells (ASCs) and olfactory ensheathing cells (OECs), was used as a therapeutic strategy after a C2 hemisection SCI in rats. Hydrogel or cells alone, and a group without treatment, were also tested. Four weeks after injury, compound muscle action potentials (CMAPs) were performed to assess functional phrenic motor neuron (PhMN) innervation of the diaphragm; no differences were observed amongst groups, confirming that the PhMN pool located between C3 and C5 was not affected by the C2 injury or by the treatments. In the same line, the vast majority of diaphragmatic neuromuscular junctions remained intact. Five weeks post-injury, inspiratory bursting of the affected ipsilateral hemidiaphragm was evaluated through EMG recordings of dorsal, medial and ventral subregions of the muscle. All treatments significantly increased EMG amplitude at the ventral portion in comparison to untreated animals, but only the combinatorial group presented increased EMG amplitude at the medial portion of the hemidiaphragm. No differences were observed in forelimb motor function, neither in markers for axonal regrowth (neuronal tracers), astrogliosis (GFAP) and inflammatory cells (CD68). Moreover, using Von Frey testing of mechanical allodynia, it was possible to find a significant effect of the group combining hydrogel and cells on hypersensitivity; rats with a SCI displayed an increased response of the contralateral forelimb to a normally innocuous mechanical stimulus, but after treatment with the combinatorial therapy this behavior was reverted almost to the levels of uninjured controls. These results suggest that our therapeutic approach may have beneficial effects on both diaphragmatic recovery and sensory function.